Evaluation of copper nanoparticles - Paraffin wax compositions for solar thermal energy storage - Lin, S.C. (Elsevier Ltd, 2016)
Phase change materials have been used extensively as thermal energy storage mediums. The low thermal conductivity of the phase change materials remains a setback and reduces the performance of gaining and releasing of the thermal energy. In this study, 20 nm copper nanoparticles were dispersed into paraffin wax to synthesis Cu-PCM nanocomposites. Five samples have been prepared to investigate the thermal properties of the produced Cu-PCM nanocomposites (Copper-Paraffin wax nanocomposites). The results of the experimental characterization showed that the thermal conductivity of the Cu-PCM nanocomposites was increased by 14.0, 23.9, 42.5 and 46.3 when 0.5, 1.0, 1.5, and 2.0 weight of nano Cu was dispersed in the PCM, respectively. The shift in the melting and solidification temperature showed that nano Cu has acted as nucleation agent to reduce the supercooling effect during the phase change process. On the analysis of the thermal degradation, nano Cu has improved the thermal stability of Cu-PCM nanocomposites without changes in chemical structure. The qualitative analysis showed that 20 nm nano Cu has hexagon shape with particles distribution size range from 15 nm to 125 nm. Site test, using integrated solar-TES system, showed efficiency enhancement by 1.7 when 1.0 nano Cu has been added to the paraffin wax. These encouraging results showed that nano Cu additive could be used to enhance the thermal properties of paraffin wax for solar thermal energy storage. Â© 2016 Elsevier Ltd.